The Tafsir of Muhammad Asad : an analytical study of his methodology - Maziah binti Mahmud (Kulliyyah of Islamic Revealed Knowledge, International Islamic University Malaysia, 2007)
Muhammad Asad is a well-known scholar whose main contribution is in the field of tafsir. The Message of the Qur'an represents his contribution towards that end. This research attempts to examine and explain all the components of the methodology applied by Muhammad Asad in his tafsir. These components as identified by the researcher are: (1) The Qur'an Interprets the Qur'an, (2) Interpretation by Highly Authentic Ahadith, (3) Identification of the Central Theme of Surah, (4) Condensation of the Contents of Surah, (5) Utilization of Some Selected Tafsir Works, (6) Deliberation over the Semantic Dimension of Words and Phrases, (7) Re-examination of the Value of the Reports on Asbab al-Nuzul, (8) Meccan and Medinan Revelations, and (9) Illustration from Judeo-Christian Sources. Some of these methods are traditional and some are novel. Muhammad Asad has thus made an enviably beautiful fusion of old as well as new techniques in unfolding the messages of the Revelation from on high. Muhammad Asad’s biographical sketch also forms a part of the thesis. Other major issues discussed in the thesis comprise the basic features of The Message of the Qur'an, and its contemporary relevance.